2006
DOI: 10.1007/s10641-006-0013-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Juvenile Habitat Use and Seasonality of Settlement by Permit, Trachinotus falcatus

Abstract: SynopsisPermit, Trachinotus falcatus are economically and ecologically important throughout their range of the Caribbean, subtropical and tropical western Atlantic, and Gulf of Mexico. Despite their economic importance, little is known about the biology and ecology of permit, and most existing information is from Florida. While sufficient information is available to paint a general picture of permit life history, details are lacking for most life stages. For the juvenile life stage, nursery habitats and size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…However, bonefish have a longer larval development period than permit. Similar models have suggested that permit spawning offshore of the Dry Tortugas, west of the Florida Keys, may be a major source of permit larvae in the region due to oceanic currents (Bryan et al ., ), yet the temporal patterns in permit larval settlement suggest larvae are also sourced from other regions (Adams et al ., ). Larval dispersal and settlement patterns of reef fishes in the Florida Keys are complex due to the influences of the timing of fish spawning and oceanic current patterns, including the formation of mesoscale eddies and tidal bores in the region between the FRT and the Florida Keys (Berger et al ., ; D'Alessandro et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, bonefish have a longer larval development period than permit. Similar models have suggested that permit spawning offshore of the Dry Tortugas, west of the Florida Keys, may be a major source of permit larvae in the region due to oceanic currents (Bryan et al ., ), yet the temporal patterns in permit larval settlement suggest larvae are also sourced from other regions (Adams et al ., ). Larval dispersal and settlement patterns of reef fishes in the Florida Keys are complex due to the influences of the timing of fish spawning and oceanic current patterns, including the formation of mesoscale eddies and tidal bores in the region between the FRT and the Florida Keys (Berger et al ., ; D'Alessandro et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In developing a comprehensive knowledge of juvenile dynamics in a fishery where there is limited data on the juvenile phase, there is a logical order in which this information can be produced. Juvenile habitats are often imperfectly known (Adams, Wolfe, Kellison, & Victor, 2006; Bradley, Baker, Nagelkerken, & Sheaves, 2019; Bradley, Baker, & Sheaves, 2017; Rooper, Boldt, & Zimmermann, 2007). First, in order to begin gathering data on any aspect of juvenile ecology, a basic census must be conducted to determine the locations where juveniles are present and the abundance or density at which they occur.…”
Section: The Role Of a Basic Juvenile Censusmentioning
confidence: 99%
“…; Adams et al . ). A nursery habitat is defined as a habitat that contributes a higher than average biomass to a spatially separated adult population compared with other juvenile habitats (Nagelkerken ; Igulu et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, these transition systems are subject to intense environmental pressures such as eutrophication, overfishing, building construction and other anthropogenic activities that lead to environmental degradation (Martinho et al 2008). These ecosystems have been referred to as fish nurseries because they harbor high densities of juvenile stages (Parrish 1989;Dorenbosch et al 2005;Adams et al 2006). A nursery habitat is defined as a habitat that contributes a higher than average biomass to a spatially separated adult population compared with other juvenile habitats (Nagelkerken 2009;Igulu et al 2014).…”
Section: Introductionmentioning
confidence: 99%